THE DEVELOPMENT OF FUTURE EFL TEACHERS' INFORMATION COMPETENCE IN PROFESSIONAL TRAINING - Yana Bondaruk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
The article explicates the significance of the development of future EFL teachers' information competence for their professional career and investigates the possibility to improve this competence in studying English. It also reveals the relations between information competence and professional development of future EFL teachers and proves that information competence has become the important one for life-long education of EFL teachers. It depicts that the information competence influences the professional level of future EFL teachers, their creative skills and abilities. In the article, compulsory and optional courses in the system of the teacher education for the development of information competence are analysed. It examines the importance of the use of information technology during professional training, as it solves not only the task to improve future EFL teachers' education but the development of the information competence of new generation school teachers. It proves that digital technologies influence the development of new ways of teaching and learning English, form new professional characteristics of EFL teachers; create new key competences for lifelong learning of future professionals. It deals with the problem that the lack of adequate access to the information and communication technology has the influence on the development of highly skilled professionals in the sphere of English language education.